L’efficacite D’un Programme Therapeutique Cognitivo-Comportemental Dans La Diminution Du Burn-Out Chez Les Infirmiers De L’hopital De Sfax (Etude Descriptive-Experimentale) - Telelaz, Galaa (European Scientific Journal, ESJ, 2018)
Burn-out result from exposure to chronic work stress, of which the caregivers and nurses are most exposed to this risk. That is why we conducted a descriptive-experimental study which is based on the quantitative approach which aims to describe the prevalence of burnout among our target population (the nurses of both public health institutions of the hospital of Sfax) and the indicators (self-esteem, coping strategy, locus of control, motivation, satisfaction, sense of self-efficacy, life orientation by a sense of coherence) that influence this syndrome and also to evaluate the effectiveness of a therapeutic program proposed and applied in this research on the reduction of the frequency of burnout. The hypotheses stipulate that there is a significant difference between the pre-test data and data collected at post-test among nurses in the experimental group. The results of our descriptive study show that 37.4% of participants suffer from high emotional exhaustion, 59.4% suffer from high depersonalization and 48.5% suffers from a sense of lack of fulfillment in their work. 31% have a degree from low to very low self-esteem, (72.5%) of participants with low levels of self-efficacy feeling an average motivation (being 50.3%) to low (being 44.8%) with 68.1% of a low amotivation, (44.8%) with a low extrinsic motivation, (47.3%) have low intrinsic motivation, (70%) are neither satisfied / nor dissatisfied, 32% have a low sense of coherence, 52.9% use coping strategies focused on emotion and (56.4%) seeking social support while (75.3%) use weakly coping strategies focused on problem solving, a majority of them uses an external attribution (44%) due to colleagues (42%) due to the superior, and also (42%) due to chance. The results of the experimental study responded generally to the research hypotheses given that they have shown significant differences between the two groups of nurses (experimental -control) post-test pre-test, which affirms the effectiveness of treatment program in reducing burnout and improving indicators.